Respostas
respondido por:
1
Resposta:
Trocamos o X por Y e temos:
y² - 6y + 8 = 0
a= 1. b = -6. c = 8
Daí é só resolver.
∆ = b² - 4ac
∆ = (-6)² - 4.1.8
∆ = 36 - 32
∆ = 4
Y = -b+-√∆ ÷ 2a
Y = -(-6)+-√4 ÷ 2.1
Y = 6+-2 ÷ 2
Y1= 6+2 ÷ 2
Y1 = 8 ÷ 2
Y1 = 4
Y2= 6 - 2 ÷ 2
Y2 = 4 ÷ 2
Y2 = 2
Lembre que achamos foi o Y e que queremos o X então:
Y = X
Y1 = X1
4 = X1
X1 = 4
Y2 = X2
2 = X2
X2 = 2
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás